The investigation of factors affecting the patient satisfaction in emergency services [Acil serviste hasta memnuniyetini etkileyen faktörlerin araştırılması] - (:unkn) unknown (Marmara University, 2013)
Objectives: The main aim of the hospitals is to retrieve the health of their patients but also to increase competition power for preserving their presence. Today, the only way to do this is by analyzing the expectations of patients and their relatives, and following up to check patient satisfaction. The purpose of this study was to identify the important factors that affect the patients satisfaction. Materials and Methods: This was a prospective crosssectional study carried out in the emergency service of a training and research hospital, in Istanbul from October 1st to November 1st, 2010. Data was collected with a questionnaire during face to face interview with the patients. SPSS v13.0 programme, t- test and ANOVA test were used for statistical analyses. Results: It was found that a total of 985 patients responded to our questionnaire study. The average age of the patients was determined as 47.03 (Maximum age: 14, Minimum age: 92). The average overall "satisfaction" of the participants was 7.58 ± 1.71 (95% CI 7.47-7.68). Conclusion: We detected that several factors play important roles in patient satisfaction. We found that the main factor is to give patient care in an organized way and consistently in emergency services.
Keywords: Emergency medicine; Patient satisfaction; Quality